KERONCONG GAYA KEEMPAT (Kajian Bentuk dan Gaya Penyajian) - Rully Aprilia Zandra (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2019)
Keroncong is a genre of music that evolves and lives in Indonesia. Many versions have been raised about the origin of keroncong. There is a version states that keroncong music was originated from Portuguese, others state that keroncong is an Indonesian local genius. Surabaya as one of the cities in Indonesia with its dinamic political development was very possible has influence to its musical history, form, and presentation style. Based on this background, the question research is how are the form and presentation style of keroncong music in Surabaya? The method used in this research was qualitative, and case study approach. The results showed that Surabaya keroncong style is charachterized by the musical forms, lyric, presentation, instruments, and tuning.